The kinetic analysis of non-isothermal carisoprodol reaction in nitrogen atmosphere using the invariant kinetic parameters method - Kamel, Laila Tosson (European Journal of Chemistry, 2014)
The non-isothermal kinetic parameters corresponding to the thermal decomposition of carisoprodol under nitrogen atmosphere was investigated at four different heating rates 5, 10, 15 and 20 °C/min. The activation energy was determined using three linear isoconversional methods, Friedman, Flynn-Wall-Ozawa and Kissinger-Akahira-Sunose. Results showed good agreement with each other. Invariant kinetic parameters (IKP) method was applied in the conversion range of 0.2 ≤ α ≤ 0.8 for the determination of the kinetic triplet. Einv= 95.81 kJ/mol, Ainv = 2.275×107 1/min and the decomposition mechanism corresponds to nucleation and growth, following the Avrami-Erofeev model, A1.5, as the kinetic model. The Perez-Maqueda et al. criterion associated with the independence of activation parameters on the heating rate (by means of Coats-Redfern and Flynn-Wall equation) confirmed the model.